Elite cohesion and the endurance of the Peruvian oligarchy - Gilbert, Dennis (2019)
Oligarchic power endured longer in Peru than in any other major Latin American nation. An oligarchy of wealthy families swayed Peruvian politics almost continuously from 1895 to 1968. Even when they did not dominate, the oligarchs exercised a powerful veto. This paper examines the resilience of oligarchic power through the lens of classical elite theory. In particular, it focuses on the problem of elite cohesion as it was tested in the aborted 1936 election.